PENGARUH PROMOSI DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI LP3I KEDIRI - Fedrianto, Alfan (JURNAL LENTERA BISNIS, 2021)
Improving buying decisions by providing promotions and service quality to consumers at LP3I Kediri. The purpose of this study was to see how promotions and services have an effect on purchasing decisions at Lp3i Kediri. The method used in this research is descriptive and verification research. Data collection techniques using questionnaires, observation and study literature. Meanwhile, the data analysis method used in this research is validity test, reliability test, path analysis, t-test, and F test using SPSS. Based on the results of the analysis carried out, it can be concluded that promotions have a positive influence on purchasing decisions by consumers, services have a significant effect on purchasing decisions and jointly promotions and services have a positive and significant impact on purchasing decisions at LP3I KEDIRI. Based on the results of this research, the steps that need to be taken by the Management of LP3I Kediri are to make further efforts to improve Purchase Decisions through improving the quality of Promotions and improving services in an intensive, continuous and coordinated manner.Keywords: Promotion, Service Quality, Buying Decision